1994
DOI: 10.1677/joe.0.1420127
|View full text |Cite
|
Sign up to set email alerts
|

The recovery of ovine pars tuberalis cells from melatonin-induced sensitization is a slow, protein synthesis-dependent phenomenon

Abstract: The pars tuberalis (PT) of the anterior pituitary is characterized by the presence of a high concentration of melatonin receptors, and acute exposure of cells from this tissue to melatonin inhibits the accumulation of cyclic AMP (cAMP) stimulated by forskolin. Conversely, exposure of ovine PT (oPT) cells to melatonin for periods of up to 16 h causes a progressive increase in subsequent basal and forskolin-stimulated production of cAMP. These observations are consistent with the possibility that the PT is invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Recently, sensitization of PT cells in terms of basal and forskolin-stimulated cAMP production as w'ell as synthe sis of secretory proteins was reported in response to chronic incubation with physiological concentrations of melatonin in vitro [40], Although prolonged exposure of the PT to melatonin seems to be functionally significant, in light of the present study it remains to be established why no putative secretory products can be found indepen dent of the photoperiod.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, sensitization of PT cells in terms of basal and forskolin-stimulated cAMP production as w'ell as synthe sis of secretory proteins was reported in response to chronic incubation with physiological concentrations of melatonin in vitro [40], Although prolonged exposure of the PT to melatonin seems to be functionally significant, in light of the present study it remains to be established why no putative secretory products can be found indepen dent of the photoperiod.…”
Section: Discussionmentioning
confidence: 56%
“…Melatonin inhibits cAMP-induced activation of protein synthesis and secretion by ovine PT cells [27,28], and there is evidence that PT cells in primary culture secrete factors that promote PRL secretion [29]. PT cells also vary their cellular response depending on the timing or duration of exposure to melatonin [30,31]. This includes the activation of the early response gene oPer1 [32]; thus the PT may have clock-like properties.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that the secretion of GNRH/LH in response to the exclusion of the inhibitory tone of endogenous opioids becomes intensified by melatonin at the cellular level. Certainly, studies on the pars tuberalis cells have revealed that cAMP is dramatically elevated following simultaneous treatment with adenylate cyclase activators and melatonin (Hazlerigg et al 1994, Barrett et al 2003. Melatonin can induce a sensitised response to adenylate cyclase in ovine pars tuberalis cells, in which the receptor for melatonin is endogenously expressed (Barrett et al 2003).…”
Section: ·2mentioning
confidence: 99%